2021
DOI: 10.3390/healthcare10010044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peroneus Longus Muscle Release on Abductor Hallucis Muscle Activity and Medial Longitudinal Arch before Toe-Tap Exercise in Participants with Flexible Pes Planus

Abstract: Pes planus is a medical condition of the foot wherein there is a flattening or lowering of the medial longitudinal arch. The abductor hallucis muscle starts at the heel bone and attaches to the medial side of the first toe. Whenever it contracts, it plays a key role in elevating the medial longitudinal arch. Hence, the abductor hallucis muscle should be strong enough to control the depression on the medial longitudinal arch. The peroneus longus muscle plantarflexes the ankle and everts the ankle and subtalar j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They also exhibited greater pelvic and trunk stability when compared with those who did not engage in this activity. This outcome conferred a greater range of mobility to the lower extremities and produced enhanced flexion traction of the knee over the hip [36], leading to improved dynamic postural stability. Studies have shown that strengthening the postural stabilizer muscles of the trunk can stimulate the functional muscular "corset" present in the center of the body by increasing the thickness or hypertrophy of the internal oblique and transversus abdominis muscles, which, in turn, improves postural stabilizer motor control.…”
Section: Discussionmentioning
confidence: 99%
“…They also exhibited greater pelvic and trunk stability when compared with those who did not engage in this activity. This outcome conferred a greater range of mobility to the lower extremities and produced enhanced flexion traction of the knee over the hip [36], leading to improved dynamic postural stability. Studies have shown that strengthening the postural stabilizer muscles of the trunk can stimulate the functional muscular "corset" present in the center of the body by increasing the thickness or hypertrophy of the internal oblique and transversus abdominis muscles, which, in turn, improves postural stabilizer motor control.…”
Section: Discussionmentioning
confidence: 99%